Nilai Pendidikan Dalam Pertunjukan Kesenian Kethek Ogleng Pacitan - sri dwi Ratnasari (Jurnal CULTURE (Culture, Language, and Literature Review), 2016)
Kethek Ogleng is one of the traditional arts from the Tokawi village, Nawangan District, Pacitan. This research aims to: (1) know the origin and development of Kethek Ogleng, (2) know the value of education in the show of “Kethek Ogleng”.  This study uses descriptive qualitative research. The results show that Kethek Ogleng dance is interesting and unique because it describes the movement of monkeys in their habitat. This dance was created by Sukiman, when he was interested in motion of the monkeys. At that time, Sukiman was looking for firewood in the forest. Storyline changed with the addition of Javanese folklore is the story about Panji Asmoro Bangun and Galuh Condro Kirono. Kethek Ogleng has the values contained in every movement and story lines, one of which is the value of education. Educational value contained in the “Kethek Ogleng” is the value of personality, character building, spiritual education and community life, providing an overview of human beings as individuals and social beings. It teaches every human to do good, hard work, tolerance, coorperation and solidarity in sosial life.   Keywords: Art, Kethek Ogleng and Value of Education.